Effects of interphases on mechanical properties of CVI-mini SiCf/SiC composites - ZHAO Wen-qing; QI Zhe; LYU Xiao-xu; JIAO Jian; MA Zhuang; ZHU Shi-zhen (Cailiao gongcheng, 2021)
BN and BN/SiC interphases were prepared on the surface of SiC tows by chemical vapor infiltration (CVI).The tows were furthered deposited a thick SiC layer to form mini SiC composites,whose tensile properties were tested.The surface and cross-section of interphase and mini-composites were observed by SEM.The surface roughness of the interphase was evaluated by AFM.The crystal structure of interphase was characterized by XRD and TEM.The results show that the BN interphase prepared by the CVI method follows Stranski-Krastanov growth mode,possessing smooth surface and weak bonds with the matrix.After heat treatment,the crystallinity and the surface roughness of BN interphase increase,and the bond with the matrix is also slightly enhanced.The BN/SiC interphase follows V-W growth mode,possessing rough surface and weak bonds with the matrix.The tensile strength of mini-composites with BN,HBN and BN/SiC interphases are 970,1050 MPa,and 1720 MPa,respectively.